Planning an intersectoral network of healthcare and community leaders to advance trans-affirming care for sexual assault survivors. Issue 2 (March 2020) - Saad, Megan; Burley, Joseph Friedman; Miljanovski, Melissa; Macdonald, Sheila; Bradley, Chett; Du Mont, Janice
Sexual assault against transgender (trans) persons is a complex public health issue requiring the coordinated effort of multiple sectors to address. In response to a global call to improve health equity for persons of diverse gender identities, leaders across health and social service sectors need to enhance collaboration to champion trans-affirming care for sexual assault survivors. In collaboration with Egale Canada Human Rights Trust and the Ontario Network of Sexual Assault/Domestic Violence Treatment Centres, we have undertaken the development of an intersectoral network to connect trans-positive community organizations with hospital-based violence treatment centres to improve support services for trans survivors across Ontario. Guided by the Lifecycle Model for network development outlined by the National Collaborating Centre for Methods and Tools, we describe our approach to planning the intersectoral network, including key insights learned thus far and the potential of the network moving forward.